Sustainability, Hedonic, Utilitarian, and Social Benefits of Car Sharing: Evidence from Tanzania - Dev Jani; John Philemon Mwakyusa (Tržište, 2022)
Purpose – Despite a boom in consumer services sharing globally, a thorough understanding of the antecedents to customer satisfaction in emerging markets is yet to be achieved. This study tested the influence of sustainability, hedonic, utilitarian, and social benefits on satisfaction derived from and behavioral intention with regard to car-sharing services in Tanzania. Design/Methodology/Approach – A total of 614 cases was subjected to variance-based structural equation modeling based on self-administered structured questionnaires to test hypothesized relationships. A combination of FIMIX-PLS and POS-PLS was used to identify unobserved heterogeneity in the sample. Findings and implications – Hedonic, sustainability, and utilitarian benefits were found to have a statistically significant effect on satisfaction and behavioral intention of car-sharing customers, while social benefits had no significant effect on both satisfaction and behavioral intention. Moreover, satisfaction is a partial mediator of hedonic, sustainability, and utilitarian effect on behavioral intention. The data showed significant unobserved heterogeneity with a four-cluster solution as optimal. Limitations – The study relied on a cross-sectional survey conducted in only one country (Tanzania), with the majority of the respondents being young people as the main embracers of the sharing economy. Originality – The study uses multi-theoretical lenses with overarching Social Exchange Theory (SET), factoring in multiple antecedents to satisfaction and intentions of using car-sharing services in a less researched sub-Saharan African context. Thus, it affirms the utility of the Social Exchange Theory, with utilitarian, hedonic, and sustainability factors having significant effects on satisfaction and intention. Practical recommendations are offered to the owners and platforms used for managing and promoting car-sharing services in the developing country context.